The Optical Refractive Correction Questionnaire (ORCQ): a face validity - Md Mustafa, Md Muziman Syah; Muzir, Nur Solehah; Ab. Halim, Noorhazayti; Yusof @ Alias, Firdaus; Hussein, Waheeda-Azwa (Universiti Putra Malaysia, 2025)
Introduction: Uncorrected refractive error is a major global public health challenge that significantly affects an individual's quality of life (QoL). Despite its impact, no validated questionnaire is specifically designed to comprehensively assess the optical correction prescriptions and characteristics for ametropic individuals. The absence of such tools prevents a thorough evaluation of the factors influencing ametropes' QoL. This study aimed to conduct a thorough face validity of the Optical Refractive Correction Questionnaire (ORCQ) to ensure its clarity, relevance, and overall quality. Materials and methods: The ORCQ serves as an instrument designed to assess the optical prescription and characteristics of correction modes worn by individuals with refractive errors. It encompasses 11 items across four domains: the optical prescription (Items 1-2), spectacle frame characteristics (Items 3-5), ophthalmic lens characteristics (Items 6-8) and contact lens characteristics (Items 9-11) currently worn by individuals with refractive errors. Face validity was carried out by six panel of experts (PEs) who are experienced optometrists. The validation criteria included evaluating grammar, clarity, and instrument layout. Quantitative responses were analysed for agreement, and adjustments were implemented based on the qualitative feedback provided by the PEs. Results: Items 1 and 2 in the optical prescription domain garnered solid agreement, confirming their clarity and appropriateness. Adjustments were made in the response box position for items 3 to 5 in the spectacle frame characteristics domain and items 6 to 8 in the ophthalmic lens characteristics domain, refining the overall layout of the instrument. In the contact lens characteristics domain, items 9 to 11 incorporated English terminologies to address clarity concerns raised by the PEs. Conclusion: The ORCQ has successfully undergone a meticulous face validity process. Therefore, it can be effectively utilised to evaluate optical correction prescriptions and characteristics among individuals wearing spectacles and contact lenses.